2009
DOI: 10.1080/01411590802707688
|View full text |Cite
|
Sign up to set email alerts
|

Lattice anharmonicity and structural evolution of LiBH4: an insight from Raman and X-ray diffraction experiments

Abstract: New in situ Raman and synchrotron X-ray diffraction data (between 300 and 400 K) in conjunction with separate temperature-dependent Raman data (between 7 and 400 K) are presented. The low-frequency Raman spectra show good agreement with theoretical values obtained previously using periodic DFT calculations. The temperature-dependent spectra reveal the presence of significant anharmonicity of librational modes neither predicted theoretically nor noted in previous experiments. The splitting of the internal defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 21 publications
(71 reference statements)
7
36
0
Order By: Relevance
“…This relation accounts for an anharmonic coupling of a reorientational motion to the deformation mode considered. This behaviour has been studied previously in the alkali borohydrides [28,29]. The corresponding results are included in table 3.…”
Section: Molecular B-h Stretching and Bending Vibrations Of The Bhmentioning
confidence: 77%
See 1 more Smart Citation
“…This relation accounts for an anharmonic coupling of a reorientational motion to the deformation mode considered. This behaviour has been studied previously in the alkali borohydrides [28,29]. The corresponding results are included in table 3.…”
Section: Molecular B-h Stretching and Bending Vibrations Of The Bhmentioning
confidence: 77%
“…B-H vibrations are readily studied by vibrational spectroscopy while the much lower energy transfers of stochastic reorientations are investigated by means of quasi-elastic neutron scattering. The structural dynamics of monometallic borohydrides have been extensively investigated by vibrational spectroscopy [28][29][30], solid state NMR spectroscopy [31][32][33][34][35], inelastic x-ray scattering IXS [36], inelastic neutron scattering INS [37], QENS [38][39][40] and recently by molecular dynamics assisted density functional theory (MD-DFT) [41,42]. The importance of the vibrational density of states for the stabilities of different polymorphs has also been discussed [43].…”
Section: Structural Dynamicsmentioning
confidence: 99%
“…It has been shown that the order parameter in LiBH 4 can be parameterized as a shift of layers formed by Li and BH 4 , together with in-layer deformations [35]. The temperature dependence of Li-B distances has shown [15] that the layers defined in the bc plane of the orthorhombic phase become flatter as the temperature is increased: the difference between atomic coordinates for Li and B atoms decreases with temperature. Also, the distance between the layers significantly increases with temperature.…”
Section: In-situ Synchrotron X-ray Diffraction Studymentioning
confidence: 99%
“…The LiBH 4 crystal structure, phase transition, and phonons modes have been investigated, mainly by X-ray diffraction [11][12][13][14][15][16][17][18], Raman spectroscopy [15,[19][20][21][22][23], NMR [18,24,25], and calorimetry [18,26].…”
Section: Introductionmentioning
confidence: 99%
“…A few light hydride systems have been studied by Rietveld methods as a function of temperature and/or pressure: these are LiBH 4 (Filinchuk et al, 2008a, c;Dmitriev et al, 2008;Hagemann et al, 2009), Mg(BH 4 ) 2 (Filinchuk et al, 2009a;Riktor et al, 2007), Ca(BH 4 ) 2 (Filinchuk et al, 2009b;Riktor et al, 2007), NaBH 4 (Kumar and Cornelius, 2005;Babanova et al, 2009), RbBH 4 , NH 3 BH 3 (Filinchuk et al, 2009c) etc. Synchrotron radiation was used in all cases, enabling rapid data collection with a fine steps in P and T. Exhaustive data analysis yielded a picture of structural evolution expressed in terms of order parameters and uncovered the P-T phase diagrams.…”
Section: Exploiting Fully In-situ Powder Diffraction Datamentioning
confidence: 99%